Evaluation of a Neonatal Resuscitation Training Programme for Healthcare Professionals in Zanzibar, Tanzania: A Pre-post Intervention Study - Xiang Ding; Li Wang; Mwinyi I. Msellem; Yaojia Hu; Jun Qiu; Shiying Liu; Mi Zhang; Lihui Zhu; Lihui Zhu; Jos M. Latour; Jos M. Latour (Frontiers Media S.A., 2021)
Background: Neonatal mortality rates remain high in Sub-Saharan African countries. Improving the newborn resuscitation skills of healthcare professionals is important in addressing this challenge. The aim of this study was to evaluate a neonatal resuscitation training programme delivered over a two-year period for healthcare professionals in Zanzibar, Tanzania.Methods: A pre- and post-intervention study was designed. We delivered neonatal resuscitation training over a 2-day period in 2017 and 2 days of refresher training in 2018. Knowledge was evaluated by a self-designed survey (11 items with a total score of 22) before and after the two training periods, and skills were evaluated by a skills checklist (six domains with 25 items with a total score of 50) completed by the trainers based on their observations. Statistical analysis included differences in the knowledge and skills scores before and after the training sessions and between the two periods.Results: A total of 23 healthcare professionals participated and completed both neonatal resuscitation training sessions. The knowledge mean scores before and after the training in 2017 increased from 9.60 to 13.60 (95% CI: −5.900; −2.099, p < 0.001), and in 2018, the scores increased from 10.80 to 15.44 (95% CI: −6.062; −3.217, p < 0.001). The mean knowledge scores post-training over time were 13.60 in 2017 and 15.44 in 2018 (95% CI: −3.489; 0.190, p = 0.030). The resuscitation skills performance between the two time periods increased from a mean of 32.26 (SD = 2.35) to a mean of 42.43 (SD = 1.73) (95% CI: −11.402; −8.945, p < 0.001).Conclusion: The neonatal resuscitation training programme increased the theoretical knowledge and resuscitation skills before and after the two training sessions and over time after a 9-month period. Continuous neonatal resuscitation training based on the local needs in resource-limited countries is essential to provide confidence in healthcare professionals to initiate resuscitation and to improve newborn outcomes.